Unravelling brand activism effectiveness: The predictors and potential effects of brand activist actions - Miguel, A.; Miranda, S. (Media e Jornalismo, 2023)
Although social issues have been considered by the business world for decades, these topics have never gained such preponderance as in the 21st century. Given the great pressures for brands to broaden their responsibilities towards society, brand activism emerges as a new strategy for companies to address relevant social-political issues, assuming a public stance on these topics and taking action to solve or improve them. However, not all brands are managing to participate in an era of activism, and even those that participate do not always get positive feedback from their stakeholders. The main objective of this article is to carry out a literature review of brand activism, developing a theoretical model of the effectiveness of brand activism that highlights the factors that contribute to the participation and success of brands in addressing social problems and the potential effects of these actions. This article thus contributes to a better understanding of the phenomenon of brand activism, concluding about useful insights for brands to achieve favorable results with their activism actions and discussing directions for future research in this field.